Test of the Effectiveness of Earthworm Flour (Lumbricus rubellus) Gastroretentive Mucoadhesive Granule Formulation on Male White Rats (Rattus norvegicus) Infected with Salmonella typhi - Magfirah; Stely Gracia Bengkati; Joni Tandi; Viani Anggi (Jurnal Penelitian Pendidikan IPA, 2024)
Lumbricus rubellus contains lumbricin which is efficacious for treating typhoid fever. The aim of the research was to determine the effectiveness of gastroretentive mucoadhesive granule preparations from earthworm flour. This study used 30 male Wistar rats which were divided into 6 groups which were given orally, the normal and negative control groups were given Na-CMC, the positive control group was given chloramphenicol, and the treatment group was given doses of 200 mg/kgBW, 400 mg/kgBW and 800 mg/kgBW. mg/kgBB gastroretentive mucoadhesive granules earthworm flour. The results of body temperature measurements, on day 7 the control group obtained results of ±37.08, ±39.00 and ±38.09 respectively, and the treatment group obtained results of ±38.09, ±38.09 and ±38.07 respectively. On day 21, the control group obtained results of ±37.08, ±39.00 and ±38.09, respectively, and the treatment group obtained results of ±38.09, ±38.09 and ±38.07, respectively. The Widal test results on the 7th day were positive and after 14 days of administering the preparation on the 21st day the results were negative. It was concluded that the effective dose for typhoid fever therapy was a dose of 400 mg/kgBW.